2007
DOI: 10.1111/j.1570-7458.2007.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect adverse effects of tomato on the predatory mite Neoseiulus californicus feeding on the spider mite Tetranychus evansi

Abstract: Plants may defend themselves against herbivores via morphological traits, chemical traits, or a combination of both. Herbivores that overcome the defensive mechanisms of a plant tend to specialize on this plant due to enhanced protection from natural enemies. Well‐known examples of plants possessing a suite of defensive mechanisms are found in nightshades (Solanaceae), especially in the tomato genus Lycopersicon. The spider mite Tetranychus evansi Baker and Pritchard (Acari: Tetranychidae) is specialized on so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 54 publications
1
26
1
Order By: Relevance
“…Tetranychus evansi is one tetranychid prey species that dramatically reduces population growth rates of P. persimilis (Escudero and Ferragut 2005). However, T. evansi only seems to be an inferior prey when it feeds on solanaceous plants, suggesting a negative bottom-up cascade caused by toxic host plant compounds (Koller et al 2007). T. urticae feeding on the same host plant species grown at different N fertilization regimes did not change the life history characteristics of P. persimilis (Bjornson and Raworth 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Tetranychus evansi is one tetranychid prey species that dramatically reduces population growth rates of P. persimilis (Escudero and Ferragut 2005). However, T. evansi only seems to be an inferior prey when it feeds on solanaceous plants, suggesting a negative bottom-up cascade caused by toxic host plant compounds (Koller et al 2007). T. urticae feeding on the same host plant species grown at different N fertilization regimes did not change the life history characteristics of P. persimilis (Bjornson and Raworth 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Prey quality can differ depending on the host plant. For example, it is known that predators may ingest accumulated or transformed harmful plant toxins by feeding on prey (de Moraes and McMurtry 1987;Escudero and Ferragut 2005;Koller et al 2007). Microscopic examination of the females at the end of the experiments revealed that their spermathecae contained spermatophores, hence they had mated.…”
Section: Discussionmentioning
confidence: 98%
“…For example, direct negative effects on the search pattern and residence time of Neoseiulus californicus (McGregor) due to glandular trichomes on S. lycopersicum have been reported (Cédola et al 2001;Kennedy 2003;Simmons and Gurr 2005). Furthermore, an indirect prey mediated effect from tomato has recently been demonstrated on N. californicus, probably due to the sequestration of toxic secondary metabolites from the plant by T. evansi (Koller et al 2007). Several studies undertaken in the past to control T. evansi using Phytoseiulus persimilis (AthiasHenriot) and N. idaeus (Denmark & Muma) have not been promising ).…”
Section: Introductionmentioning
confidence: 95%